2008
DOI: 10.1016/j.visres.2008.04.014
|View full text |Cite
|
Sign up to set email alerts
|

The organization of spatial frequency maps measured by cortical flavoprotein autofluorescence

Abstract: To determine the organization of spatial frequency (SF) preference within cat Area 17, we imaged responses to stimuli with different SFs using optical intrinsic signals (ISI) and flavoprotein autofluorescence (AFI). Previous studies have suggested that neurons cluster based on SF preference, but a recent report argued that SF maps measured with ISI were artifacts of the vascular bed. Because AFI derives from a non-hemodynamic signal, it is less contaminated by vasculature. The two independent imaging methods p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
(55 reference statements)
3
3
0
Order By: Relevance
“…Such a relationship is regarded as a way to achieve uniform coverage, so that all combinations of respective parameters are equally represented across the cortical surface (Swindale et al, 2000). A model with orientation pinwheel centers located at the center of domains coding for extreme SFs is consistent with this view (Issa et al, 2000(Issa et al, , 2008. In contrast, our data indicates that isoorientation and iso-SF lines tend to run parallel to each other.…”
Section: Spatial Frequency and Orientation Maps Underlie The Same Funsupporting
confidence: 90%
See 1 more Smart Citation
“…Such a relationship is regarded as a way to achieve uniform coverage, so that all combinations of respective parameters are equally represented across the cortical surface (Swindale et al, 2000). A model with orientation pinwheel centers located at the center of domains coding for extreme SFs is consistent with this view (Issa et al, 2000(Issa et al, , 2008. In contrast, our data indicates that isoorientation and iso-SF lines tend to run parallel to each other.…”
Section: Spatial Frequency and Orientation Maps Underlie The Same Funsupporting
confidence: 90%
“…It is characterized by the coexistence of a global anteroposterior gradient and local patches typical of the representation of other visual attributes such as orientation. In A17, the existence of such patches is consistent with previous optical imaging studies Everson et al, 1998;Issa et al, 2000;Mallik et al, 2008;Tani et al, 2012). In A18, the present study extends and provides further detail to the recent observation that SFs of 0.15, 0.08, and 0.04 cpd preferentially activate different cortical locations (Tani et al, 2012).…”
Section: Existence Of Spatial Frequency Maps In Visual Cortexsupporting
confidence: 90%
“…Another recent optical imaging study refuted the idea of a columnar organization for spatial frequency preference (Sirovich & Uglesich, 2004). Finally, a latest autofluorescence imaging study confirmed the existence of the spatial frequency map (Mallik et al, 2008). The present results are in agreement with the existence of spatial modulations of the preferred spatial frequency in area 17.…”
Section: Organization Of Spatial Frequency Preferencesupporting
confidence: 87%
“…Thus, in the present study, the contribution of the hemodynamic coupling in the overestimation of optimal diameter values has been limited. Interestingly, the recent advances made in the field of flavoprotein autofluorescence functional imaging could provide an alternate, and more specific, method to confirm the existence of this new cortical organization in the future (Husson et al, 2007; Mallik et al, 2008; Sirotin and Das, 2010). …”
Section: Discussionmentioning
confidence: 99%